Studying The Effects of Perceived Organizational Justice in The Management Control System On Unethical Behaviors in Budgeting, Considering The Role of Psychological Dimensions - Ramin Zeratgari; Gholamreza Rezaei; Mehran Farahmand (پژوهش‌های مدیریت عمومی)
Abstract The occurrence of unethical behavior, especially in government and public organizations, has become a challenge. The purpose of this study is to investigate the effect of perceived organizational justice in the management control system on unethical behaviors in budgeting with emphasis on considering the role of psychological dimensions.This research is applied in terms of purpose and descriptive-survey in terms of implementation with structural equation modeling approach. The statistical population is the managers of the University of Medical Sciences and hospitals in Sistan and Baluchistan province. The sample was determined using Morgan's table, 169 persons were selected using simple random sampling method. The data collection tool is a questionnaire. The results show that the evidence obtained in reducing unethical behaviors is largely contradictory; So that participation in setting goals, using different performance indicators and the quality of feedback have a positive and significant effect on the desire to create a budget slack; While using the principle of controllability does not have a significant effect on creating a budget slack. The results of the path analysis show that organizational commitment has a negative and significant effect on creation of budget slack and data manipulation. Another result is that the effect of trust in superiors on the creation of budget slack is positive and significant. In addition, participation of managers in determining the goals and the principle of controllability do not have a significant effect on data manipulation, and the use of different measures of the organization's performance and the quality of feedback have a negative and significant effect on data manipulation.Introduction In recent years, the increasing attention to the issue of organizational justice and its effects on organizational performance has led organizations to use different models and methods to achieve their goals and continue their existence and gain a new competitive advantage. Be safe from falling, overturning and dangers caused by rapid environmental changes. Organizational justice is socially constructed and affects people's attitude and behavior in the workplace. Organizational justice refers to employees' understanding of what they consider to be fair or unfair in their work environment. Therefore, organizational justice, which is also called organizational fairness, is the fairness that employees perceive about working relationships within the organization.Research has been done to identify how the elements that increase the feeling of injustice and the main reactions of people occur. Langevin and Mendoza (2013) emphasize, if the management control system (MCS) is considered unfair, it can lead to behaviors in managers that are harmful to the organization. For example, this may lead managers to unethical behaviors such as a tendency to create budgetary slack and manipulate data.Case study In this study, the data obtained from the educational and therapeutic institutions of the Ministry of Health, Treatment and Medical Education of Sistan and Baluchistan province (universities of medical sciences of Sistan and Baluchistan province and affiliated hospitals) have been used.Materials and Methods The statistical population used in this study is the managers of the University of Medical Sciences and the heads of affiliated hospitals of Sistan and Baluchistan province, the number of the statistical population in this study is 300 people. In this study, the sample size was determined using Cochran's formula, and the questionnaire was administered online through Google Form to more than 200 middle and senior managers. Among these people, 171 people answered all the questions and the information of 169 people can be analyzed, as it is in accordance with the sampling method based on Morgan's table. Structural equation modeling (SEM) and PLS software will be used to test the hypotheses.Discussion and Results The results of this study show that the role of participation in setting goals on increasing the perceived distributive justice in MCS is not significant. Also, participation in setting goals has a significant relationship with procedural justice. The quality of feedback is significantly related to the procedural and interactive justice of the management control system. In addition, the results indicate the significant impact of multiple performance indicators on distributive and procedural justice. The results show that three of the dimensions of the management control system; That is, participation in setting goals, using different performance measures and the quality of feedback have a positive and significant effect on create a budgetary slack; While application of the controllability principle does not have a significant effect on creation of budgetary slack. The results of the path analysis show that organizational commitment has a negative and significant effect on the two variables of unethical behavior, creation of budgetary slack and data manipulation. While the results show that the dimensions of the management control system do not reduce the creation of budgetary slack. Another result is that the effect of trust in superiors on the creation of budgetary slack is positive and significant. The obtained evidence shows that managers' participation in determining goals and the principle of controllability do not have a significant effect on data manipulation, and the use of different organizational performance measures and the quality of feedback have a negative and significant effect on data manipulation.ConclusionIn the past two decades, a large number of scandals have occurred in non-profit organizations, government or business enterprises, many of them related in various ways to accounting and management control systems. Understanding the inefficient effects of measurement systems and incentives and possible ways to overcome such inefficient effects is essential. Therefore, it is interesting to search for explanations and justifications about possible unethical behaviors in relation to the components of the management control system in organizations, because the result obtained may be one of the roots of many scandals.